Rationally designed three-dimensional porous NiCo2N@C reticular structure for high-performance Li-ion batteries. (September 2020) - Wang, Peiyao; Zhao, Bangchuan; Bai, Jin; Li, Kunzhen; Ma, Hongyang; Li, Wanyun; Zhu, Xuebin; Sun, Yuping
Abstract: Three-dimensional (3D) porous NiCo2 N@C composite was deposited on nickel foam substrate through the electrostatic spray deposition (ESD) technique followed by a post-annealing process under ammonia atmosphere. The prepared reticular-structured NiCo2 N@C film used as binder-free anode for lithium-ion batteries (LIBs) can exhibit excellent electrochemical performance. It delivers high initial discharge capacity of 1215.8 mAh g −1 at a current density of 1 A g −1 and can reach 1630.9 mAh g −1 after 400 cycles. The electrode also shows a superior rate capability with 955.4 mAh g −1 at 10 A g −1 current density. Graphical abstract: Image, graphical abstract